2013
DOI: 10.1175/jcli-d-12-00315.1
|View full text |Cite
|
Sign up to set email alerts
|

Weakening of the Kuroshio Intrusion into the South China Sea over the Past Two Decades

Abstract: Inferred from the satellite and in situ hydrographic data from the 1990s and 2000s, the Kuroshio intrusion into the South China Sea (SCS) had a weakening trend over the past two decades. Associated with the weakened Kuroshio intrusion, the Kuroshio loop and eddy activity southwest of Taiwan became weaker, whereas the water above the salinity minimum became less saline in the northern SCS. The sea surface height southwest of Taiwan increased at a slower rate compared to other regions of the SCS because of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 45 publications
3
57
0
Order By: Relevance
“…The Kuroshio intrudes into the SCS through the LUS, carrying the warm and salty water from the NWP, significantly affecting the circulation pattern and the budgets of heat and salt in the NSCS (Farris and Wimbush, 1996;Wu and Chiang, 2007;Liang et al, 2008;Nan et al, 2013). However, this is still not in accordance with how the Kuroshio intrudes into the NSCS.…”
Section: Introductionmentioning
confidence: 99%
“…The Kuroshio intrudes into the SCS through the LUS, carrying the warm and salty water from the NWP, significantly affecting the circulation pattern and the budgets of heat and salt in the NSCS (Farris and Wimbush, 1996;Wu and Chiang, 2007;Liang et al, 2008;Nan et al, 2013). However, this is still not in accordance with how the Kuroshio intrudes into the NSCS.…”
Section: Introductionmentioning
confidence: 99%
“…The minimum distance between cruise stations is approximately 20 km, which is within the Rossby radius of deformation of both the ocean (~20-120 km; Cai et al 2008) and atmosphere (10-200 km, with the time scale from hours to days for mesoscale processes; Fujita 1981). Subsequently, the observations from these cruises and fixed stations have been capable of resolving mesoscale processes, such as eddies (Nan et al 2011;He et al 2013), fronts , and coastal upwelling (Wang et al 2013a) in the ocean, as well as synoptic weather processes such as cold surges and tropical cyclones in the atmosphere. For example, Li et al (2006) investigated the impact of cold surge on SST and air-sea heat fluxes.…”
Section: Multi-institution Collaborationmentioning
confidence: 96%
“…Then, from 1989 to 1999, several cruises took place and yielded larger datasets for the southern SCS (SSCS) (Fang et al 2002). At that time, there were only a few cruise stations in the central SCS (between 12° and 18°N) and around the dynamically energetic regions (e.g., west of the Luzon Strait and east of the Vietnam coast), where mesoscale eddies are active (G. Chen et al 2010;Zhuang et al 2010;Nan et al 2011). Most of these earlier observations did not include meteorological observations, consisting only of conductivity-temperature-depth (CTD) measurements in the ocean.…”
Section: Earlier Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-basin pressure gradient between the northwest Pacific Ocean and the SCS is suggested be an important mechanism influencing the LST and hence the SCSTF. Nan et al (2013) showed that the pressure gradient between these two basins has a negative trend in last two decades. The basin-mean rate of sea level rise in the SCS during 1993-2012 is 5 mm year −1 and about 72 % (3.6 mm year −1 ) of the total sea level rise is contributed by the PDO (Cheng et al 2015).…”
Section: Implications Of the South China Sea Throughflowmentioning
confidence: 99%